1995
DOI: 10.1002/dc.2840120215
|View full text |Cite
|
Sign up to set email alerts
|

Pilomatrixoma: A description of two cases diagnosed by fine‐needle aspiration

Abstract: The present work reports on the findings obtained by fine-needle aspiration of two pilomatrixomas located on the upper limbs whose diagnosis was confirmed histologically. In both cases, the cytology disclosed a proliferation of small round basaloid cells that were dispersed and grouped in clusters together with squamous cells and abundant multinucleate giant cells. The differential diagnosis with other neoplasms is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
1

Year Published

1997
1997
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 5 publications
0
11
1
Order By: Relevance
“…Since Woyke et al reported the cytology of 6 cases in 1982, 16 there have been only 22 additional cases reported. Of these 28 cases, not more than 10 were correctly diagnosed prior to excision, 6,8,9,11,13,14 and 10 were misinterpreted as carcinoma or suspicious for carcinoma 6,7,15,16 -1 as basal cell carcinoma (BCC), 8 1 as pleomorphic adenoma with squamous metaplasia 3,4 and 1 as neoplasm, not otherwise specified. 8 In two cases specific cytologic diagnoses were not tendered, 1,3 and in three cases FNA diagnoses were not mentioned in the reports.…”
mentioning
confidence: 99%
“…Since Woyke et al reported the cytology of 6 cases in 1982, 16 there have been only 22 additional cases reported. Of these 28 cases, not more than 10 were correctly diagnosed prior to excision, 6,8,9,11,13,14 and 10 were misinterpreted as carcinoma or suspicious for carcinoma 6,7,15,16 -1 as basal cell carcinoma (BCC), 8 1 as pleomorphic adenoma with squamous metaplasia 3,4 and 1 as neoplasm, not otherwise specified. 8 In two cases specific cytologic diagnoses were not tendered, 1,3 and in three cases FNA diagnoses were not mentioned in the reports.…”
mentioning
confidence: 99%
“…Microfilariae have been observed in various cytologic materials, like aspirates from breast, 7 bone marrow, 9 thyroid, 8,10 epididymis, 4 and exfoliated material, like cervicovaginal smears, 3 urine, 5 effusions, and bronchial and laryngeal brushings. 2 Various neoplasms, like meningioma, hemangioblastoma, retroperitoneal fibromyxoma, osteoclastoma, metastatic carcinoma of the scapula and carcinoma of the cervix, 1 have also been associated with the incidental presence of microfilariae.…”
Section: Microfilariae In Fine Needle Aspiration Smears From Lesions mentioning
confidence: 99%
“…Remains of acellular, eosinophilic material and some giant multinucleated cells can also be found. 5,[8][9][10] This case is of interest for several reasons. Due to the rarity of pilomatrixoma in the breast, the possibility of this type of lesion is often overlooked.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations